If it's not what You are looking for type in the equation solver your own equation and let us solve it.
-3(4-2x)+8=5+3x
We simplify the equation to the form, which is simple to understand
-3(4-2x)+8=5+3x
Reorder the terms in parentheses
+(-12+6x)+8=5+3x
Remove unnecessary parentheses
-12+6x+8=+5+3x
We move all terms containing x to the left and all other terms to the right.
+6x-3x=+5+12-8
We simplify left and right side of the equation.
+3x=+9
We divide both sides of the equation by 3 to get x.
x=3
| -38-37a+39a=1+5a | | x-1.4=0.6 | | (2x+1)/(4x-3)=3/4 | | t^2=100-20t | | 5(1+-2z)=3(3z+-4) | | 5n+9=-46 | | 50k+66=141+75k | | 4/3=8/x-1 | | 6(5x+-13)=12(x+4) | | -3+3n=1-n | | (5x+1)/x*(4y+3)/4=20 | | 1-x=-9+2x+2x | | -9=b-5 | | 7x(9+6)=12 | | 9(k-4)-7k=32-2(k+5) | | 6+b=3b+4 | | x+.5x+.75x+1=100 | | -v=-3v+2v | | 1x-3=3x-15 | | x+.5x+.75x=100 | | 4-(x-3)=5x+1 | | 3x+2x+(x+12)+(2x+4)=180 | | x+5=-4x+10 | | FV=1800(1.00667)24 | | 2(3p-4)-3(5-2p)+18=19 | | 0.77= | | 2(3P-4)-3(5-29)+18=19 | | -4x+6=2x+2 | | 2b=-6 | | 5(2x-1)=6x+2 | | 96=1x*10 | | 114-6x=9x-4 |